LEVERAGING A CENTRALIZED FLEET ASSIGNMENT MANAGEMENT FOR AN AVIATION RESILIENCE - Acton, Inof Seno, Mr.; Soehodho, Sutanto; Yusuf, Nahry (Smart City, 2026)
Since deregulation in the aviation industry, competition among airlines has intensified. This competition is shown by the increasing number of routes, service times, aircraft, and airports served. This competition causes not all flight services to meet their targets, resulting in aircraft operating less efficiently. Passenger seats are not filled, and flight delays are becoming more frequent. Obviously, this will negatively impact consumers and the airline's finances. The study focused on assigning the fleet used to serve flights to maintain existing aviation services and improve aircraft operational efficiency. This study aims to maximize profits by optimizing fleet assignments through the Centralized Fleet Assignment Management (CFAM) strategy. In general, airlines regulate the assignment of their respective fleets. However, in this CFAM, the fleet assignment strategy is carried out centrally by a single management, as if it were a joint company. Integer Programming was used in this study to optimize the aviation fleet assignment model. The purpose of this model is to determine the most appropriate fleet for flights to maximize profits. The results of the study show that the CFAM strategy generates higher profits than in previous conditions, and the aircraft assignment composition is also obtained. With this strategy, evidently, airlines as a system will benefit financially, helping them avoid potential bankruptcy that could have serious consequences for flights. The strategy also offers a different perspective and new nuances to flight service management. In addition, the most important result of this study is that it can serve as a basis for government policy, in this case as a regulator of air transportation services, to ensure the continued operation of aviation services.